2007
DOI: 10.1124/jpet.107.120709
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Ephedrine Alkaloids on Human α1- and α2-Adrenergic Receptor Subtypes

Abstract: Ephedra species of plants have both beneficial and adverse effects primarily associated with the presence of ephedrine alkaloids. Few reports have appeared that examine the direct actions of ephedrine alkaloids on human subtypes of adrenergic receptors (ARs). In the present study, ephedrine alkaloids were evaluated for their binding affinities on human ␣ 1A -, ␣ 1B -, ␣ 1D -, ␣ 2A -, ␣ 2B -, and ␣ 2C -AR subtypes expressed in HEK and Chinese hamster ovary cells. Cell-based reporter gene assays were used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 20 publications
0
46
0
1
Order By: Relevance
“…Nasr and Shariati (2005) reported that different concentrations of ephedrine reduced the seed germination of Astragalus cycluphyllus. Ephedrine exhibits optical isomerism and has two chiral centers, giving rise to four stereoisomers; by convention, enantiomers with opposite stereochemistry around the chiral centers are designated as ephedrine, while pseudoephedrine has same stereochemistry around the chiral carbons (Ma et al 2007). A reduction in seed germination of perennial ryegrass was consistent with different concentrations of the stock Ephedra extract (Fig.…”
Section: Ephedramentioning
confidence: 56%
“…Nasr and Shariati (2005) reported that different concentrations of ephedrine reduced the seed germination of Astragalus cycluphyllus. Ephedrine exhibits optical isomerism and has two chiral centers, giving rise to four stereoisomers; by convention, enantiomers with opposite stereochemistry around the chiral centers are designated as ephedrine, while pseudoephedrine has same stereochemistry around the chiral carbons (Ma et al 2007). A reduction in seed germination of perennial ryegrass was consistent with different concentrations of the stock Ephedra extract (Fig.…”
Section: Ephedramentioning
confidence: 56%
“…24,25) In contrast, ephedrine alkaloids are known to express their pharmacological actions via the α-and β-adrenergic receptors, and are reported to induce release of endogenous catecholamines, such as noradrenaline and dopamine, indirectly and to prevent their neuronal reuptake. 26) Noradrenaline is one of the most abundant neurotransmitters in the central and peripheral nervous systems, and is implicated in many aspects of physiology and behavior, including cognition, attention, reward, locomotion, and arousal. Smallmolecule activators of noradrenaline signaling have been shown to increase wakefulness, whereas inhibitors promote sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based receptor gene assays were used to establish functional activity of ephedrine alkaloids at α1A, α2A, and α2C adrenergic receptors. 40 Previously, Vansal and Feller (1999) also evaluated direct effects of the ephedrine isomers on human β1, β2, and β3 adrenergic receptors expressed in Chinese hamster ovary cells.…”
Section: Studies Showing Direct Mechanism Of Action Of Ephedrinementioning
confidence: 99%